Public Perceptions of Disability-Friendly Services in the City of Cirebon - Amalia Rokmah; Siti Khumayah (Green Publisher Indonesia, 2026)
One of the significant measures of local government performance in terms of social justice and public value is the provision of disability-friendly public services. This paper examines the public value of disability-friendly public services in Cirebon City through the Public Value theory of Mark Moore, which focuses on social legitimacy, operational capacity, and substantive value. This study employed a qualitative descriptive approach by conducting in-depth interviews with local government agencies and disability community organizations, supported by policy document analysis and field observations. The findings indicate that Cirebon City has succeeded in improving disability services through community involvement, enhanced accessibility facilities, and skills training programs. Nevertheless, several challenges remain, including inter-agency coordination, program sustainability, and the capacity of officials to address the specific needs of persons with disabilities. Therefore, strengthening institutional collaboration and social communication is necessary to ensure the long-term sustainability of these policies. This research concludes that human-centered public services represent the actualization of public value based on social legitimacy through collaborative governance.